PHENOTYPIC CORRELATIONS BETWEEN SOME EXTERNAL AND INTERNAL EGG QUALITY TRAITS IN THE JAPANESE QUAIL (Coturnix coturnix japonica) - DUDUSOLA, I. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This study aimed to determine the internal and external quality traits of the Japanese quail eggs as well as the phenotypic correlation between these traits. Measurement were taken on 1796 Japanese quail eggs obtained from 400 females and 200 males in an experiment conducted at the Quail Unit of Centre Songhai, Porto-Novo, Benin Republic. The data was analysed using PROC SAS. Values of egg weight, egg length, yolk height, albumen height, shell thickness, egg diameter, shape index and Haugh unit were found as 11.21g, 3.17cm, 7.82cm, 1.08cm, 0.58cm, 0.19mm, 2.49cm, 1.27 and 60.13, respectively. Significant (P<0.001) correlation values were obtained between albumen height and yolk height; and albumen height and Haugh unit. There was a negative but significant correlation between egg weight and Haugh unit (-0.90). Phenotypic correlations of external quality traits showed that most of the traits considered were positively correlated (P<0.001). The results showed that as the egg weight, egg length, egg circumference, shell thickness, egg diameter and shell index increase, the Haugh unit decreases. Most of the external and internal quality traits showed high positive correlations, thus could be easily improved upon. Based on the negative correlation observed between Haugh unit and egg weight in this study, it could be said that increase in egg weight will cause a decrease in Haugh unit which is a quality indicator of eggs.